Analisis Kemampuan Komunikasi Matematis Siswa Sekolah Menengah Atas pada Materi Lingkaran - Faizal Amin Nur Yunus; Shanti Nurhidayah (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2025)
This study analyzed high school students' mathematical communication skills on circle problems based on three categories: high, medium, and low. The research method used was qualitative with a descriptive approach. Data were collected through written tests and interviews to determine students' understanding and how they communicated their thinking processes in solving circle problems. The results showed that students with high ability were able to answer correctly and explain systematically. Students in the medium category understood most of the concepts but were less coherent in their explanations. Meanwhile, students in the low category had difficulty understanding the concepts and explaining their answers. These findings emphasize the importance of mathematical communication in mathematics learning. Therefore, it is recommended that learning emphasize discussion and the delivery of ideas to improve student understanding.